Analisis Faktor-Faktor yang Mempengaruhi Permintaan Daging Ayam Broiler di Provinsi Bali - Aryani, Gusti Ayu Dwiti; Jember, I Made (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 8, No. 5, Mei 2019, pp (945-1180), 2019)
The demand for chicken meat has fluctuations every year, where demand for chicken meat is influenced by several factors such as price, prices of other goods, income per capita, and population. This study aims to determine the effect of prices, prices of other goods, per capita income, and population on the demand for broiler chicken meat. The data collection method used is a non-participant observation technique, while the data analysis method used is multiple linear regression with the help of the Eviews program. The results of this study indicate that the price of chicken meat partially gives a negative and significant effect on the demand for broiler chicken in Bali Province, the price of other goods partially gives a negative and not significant effect on the demand for broiler chicken in Bali Province. Whereas per capita income and population have a positive and significant effect on the demand for broiler chicken in the Province of Bali. The results of this study are expected to be able to provide information for the government to be able to provide a policy of increasing prices of basic necessities such as chicken meat so that later it can improve people's welfare.